LOCAL GOVERNMENT ADAPTATION STRATEGIES IN FACING CLIMATE CHANGE: AN INNOVATIVE FRAMEWORK - Warouw, Felly Ferol; Waty, Reni Rentika; Mayasari, Yane; Syam, Abd. Rahman; Muksin, Isra (Alqaprint Jatinangor, 2023)
In the face of escalating climate change challenges, this study presents an innovative framework for local government adaptation strategies, emphasizing the integration of scientific research and policy-making. Through a comprehensive analysis of existing adaptation models and the incorporation of case studies from diverse geographical regions, the paper identifies key factors influencing effective local government responses to climate change. The proposed framework highlights the importance of community engagement, resource allocation, and sustainable development practices in enhancing resilience. By evaluating the effectiveness of various adaptation strategies, the study offers insights into best practices and potential pitfalls, aiming to guide local governments in developing tailored approaches to climate change challenges. The findings underscore the necessity for a dynamic, multi-stakeholder approach, bridging the gap between theoretical understanding and practical implementation of climate adaptation measures.